The Effects of Blame Attributions and Offender Likableness on Forgiveness and Revenge in the Workplace - Bradfield, Murray; Aquino, Karl (Journal of Management, 1999)
This study proposes and tests a model that applies the concept of restorative justice to the enactment of revenge and forgiveness in organizations. The model draws from theories of cognitive attribution and consistency, as well as more recent theories of revenge in organizations, to describe the process by which a personal offense triggers revenge and forgiveness cognitions and behavior. Attributions of blame were predicted to directly influence the contemplation of revenge and forgiveness strategies. In turn, these cognitions were hypothesized to be the immediate precursors of behavior. It was also predicted that the likableness of the offender would be positively associated with both revenge and forgiveness cognitions. Finally, blame attribution was expected to be influenced by offense severity. To test these predictions, a survey was administered to one hundred and eighty employees of a government agency. Structural equation modeling was used to assess the significance of the pathways in the model and compare its fit to theoretically plausible rivals. Although the theoretical model fit the data well, a less constrained alternative showed a superior fit. In both the theoretical model and less constrained alternative, all but two of the predicted pathways in the model were upheld. The implications of the findings for organizations are discussed and future research directions are offered.